ANALYSE DE L’EXECUTION DES BUDGETS DE RECETTES DE LA PROVINCE DU MANIEMA DE 2012 A 2014 - MUPASA, MUPASA BIN (IJRDO - Journal of Business Management, 2022)
Executing revenue budgets is a very delicated task for any organization. With regard to the Province of Maniema, the results of this research reveal that despite its enormous potential in naturel resources and the creation of the General Direction of Receipts of Maniema, DGRMA in acronym, it does note manage to research the level of this revenue forecasts to properly cover its expenses.Indeed, during the three years selected for this research, the rate of annual achievement of the revenue compared of their respectives forecasts varied from one year to another, for values well below 50%, a strong signal of the ineffectiveness of revenue budgets in this province.The general trend of the evolution of these rates during these three years is upwards, despite the poor performance observed. This increase is too low, estimated at 0,0177 congolese francs per year.